2019
DOI: 10.1002/ps.5493
|View full text |Cite
|
Sign up to set email alerts
|

Additive interaction between a root‐knot nematode Meloidogyne javanica and a root‐feeding flea beetle Longitarsus bethae on their host Lantana camara

Abstract: BACKGROUND Changes in plants induced by one species have indirect effects on interactions with other species, thus shaping their abundances. The root‐feeding beetle Longitarsus bethae released as a biological control agent for Lantana camara has established at a few sites in South Africa. Lantana camara plants infected with the root‐knot nematode Meloidogyne javanica often exhibit an increase in L. bethae abundance, suggesting that nematode‐infected plants could be enhancing the development of the beetle. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…The ecological relevance of how herbivore impacts combine is obvious, both from a basic and an applied perspective. For instance, information on nonadditivity could help inform policies on pest suppression in agricultural crops (Barber et al 2012;Gagic et al 2016) and strategies for biological control of weeds by herbivorous insects (Wooley et al 2011;Musedeli et al 2019). More contentious, however, is the issue of whether nonadditivity of herbivore impact is relevant to the evolution of host plants.…”
Section: Introductionmentioning
confidence: 99%
“…The ecological relevance of how herbivore impacts combine is obvious, both from a basic and an applied perspective. For instance, information on nonadditivity could help inform policies on pest suppression in agricultural crops (Barber et al 2012;Gagic et al 2016) and strategies for biological control of weeds by herbivorous insects (Wooley et al 2011;Musedeli et al 2019). More contentious, however, is the issue of whether nonadditivity of herbivore impact is relevant to the evolution of host plants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study showed that a root-eating flea beetle Longitarsus bethae performed better on Lantana camara plants infected with M. javanica than on plants with healthy roots (Musedeli, 2020). On the other hand, other study showed that soybean cyst root nematode Heterodera glycine negatively affects the above-ground leaf-chewing Spodoptera litura by increasing the developmental time and decreasing adult body weight .…”
Section: Introductionmentioning
confidence: 99%